Ability of steel fibers to enhance the shear and flexural behavior of high-strength concrete beams subjected to blast loads. (15th November 2019) - Algassem, Omar; Li, Yang; Aoude, Hassan
Highlights: Ten high-strength fiber reinforced beams are tested under quasi-static and blasts loading. Effects of steel fiber, fiber type/content, and combined use of stirrups are investigated. Use of steel fiber enhances blast resistance & damage tolerance and improves control of displacements. Results show fibers with le aspect ratio is more effective. Beam response is predicted using dynamic inelastic SDOF analysis. Abstract: The provision of steel fibers improves many of the properties of high-strength concrete (HSC), including its tensile capacity, ductility, toughness and fragmentation resistance. These enhanced features also make high-strength fiber reinforced concrete (HSFRC) an ideal material for the blast resistant design of structures. One of the established applications of fiber-reinforced concrete is in beams, where fibers can be used to increase shear capacity and replace transverse reinforcement. While extensive research exists on the behavior of FRC and HSFRC beams under static loads, studies examining the blast behavior of such beams is scarce. Accordingly, this paper presents the results of an experimental program which studies the effect of steel fibers on the blast performance of high-strength concrete beams. As part of the study, ten HSFRC beams are tested under either static loads or simulated blast loads using a shock-tube. Test variables include the effects of fibers, fiber content, fiber type, longitudinal steel ratio and combined use of fibers and transverse reinforcement. The results show that the use of fibers in HSC beams increases blast resistance, improves control of displacements and results in superior damage tolerance. In addition, the results show that steel fibers can substitute for transverse reinforcement and prevent blast-induced shear failures. The analytical investigation shows that the use of SDOF analysis, with development of non-linear resistant functions, can be used to predict the blast response of HSFRC beams with good accuracy.